Dictionaries as Representations of the State of the Social Professions - Some Preliminary Observations from an Italian Perspective - Annamaria Campanini (Social Work and Society, 2006)
Italian social Work has experienced in the last decades a boost in terms of greater visibility and legitimacy making it emerge from the shadows where it had lingered for forty years and more. The process of regulating social work education through ministerial decrees in line with other disciplines has resulted in a three-year degree in 'sciences of Social Work' ('servizio sociale', first level degree), a Master's Degree in 'planning and Management of Politics and Social Services' (second level degree), and study programmes at doctoral level. Linked to this, there has been the drawing up of a professional register, of a code of ethics for social workers, and a regulation for professional confidentiality. Hence, we can affirm that, by sociological criteria, social work has become today a recognised profession.